Multimorbidity and risk of falls, fractures, and joint replacements over two decades: Findings from the Hertfordshire Cohort Study - Westbury, LD; Pearse, C; Rambukwella, R; Ward, KA; Cooper, C; Dennison, EM (Wiley, 2024)
Aim: To examine the relationship between level of morbidity burden and long‐term risk of fractures, falls, and joint replacements in the community‐dwelling participants of the Hertfordshire Cohort Study. Methods: Data were analyzed from 2997 individuals (age 59–73 at baseline). Outcomes (fractures, falls, and lower limb joint replacements) were identified using ICD‐10 and OPCS‐4 codes from Hospital Episode Statistics data, available from baseline (1998–2004) until December 2018. Number of systems medicated (marker of morbidity level) in relation to risk of outcomes was examined using sex‐stratified Cox regression. Results: Among both men and women, a greater number of systems medicated was related to increased risk of falls (P < 0.001) and lower limb joint replacements (P < 0.003). More systems medicated was only related to increased risk of fracture among women (P‐values for trend of <0.001 among women and 0.186 among men). Conclusions: Higher morbidity was associated with increased risk of adverse health outcomes related to poor musculoskeletal health, but these relationships varied according to the musculoskeletal outcome studied. Intervention strategies to reduce multimorbidity among middle‐aged and older people may hence reduce the burden of musculoskeletal aging. Geriatr Gerontol Int 2024; ••: ••–••.